The role of central banks in financial inclusion and sustainable development: comparative analysis of Islamic and conventional banking environments (2018)
Several findings established the importance of Islamic finance through the removal of collateral and the payment of interest that are features of conventional banking in guaranteeing increased financial inclusion, economic growth and diversification, poverty alleviation!, enhanced efficiency of intermediation and increase income per worker, among others. Financial exclusion is attributed to religion, economic inequality, culture, geography and structure of the economy, lack of access to loans, deposit services, insurance, pension, and financial illiteracy. Therefore, this paper examines the roles of central banks in creating financial inclusion in conventional and Islamic banking environments with a view to drawing important lessons for economies struggling with challenges of financial inclusion in multi religious states like Nigeria. The paper uses comparative contextualization and analyses trends of financial inclusion indicators as outcomes of central bank policy design and implementation strategies in these different paradigms to draw inferences of efficiency and effectiveness. The paper posits that Central Banks in Islamic banking environments which imbibe and actively implement financial inclusion strategies generate better outcomes relating to access to loans, deposit services, insurance, pension, and financial literacy.